2003
DOI: 10.1037/0096-1523.29.3.523
|View full text |Cite
|
Sign up to set email alerts
|

Recalibrating the auditory system: A speed-accuracy analysis of intensity perception.

Abstract: Recalibration in loudness perception refers to an adaptation-like change in relative responsiveness to auditory signals of different sound frequencies. Listening to relatively weak tones at one frequency and stronger tones at another makes the latter appear softer. The authors showed recalibration not only in magnitude estimates of loudness but also in simple response times (RTs) and choice RTs. RTs depend on sound intensity and may serve as surrogates for loudness. Most important, the speeded classification p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 40 publications
2
39
1
Order By: Relevance
“…The general consensus, therefore, seems to be that there is a close relationship between loudness and RT. Consequently, it has been proposed that RT may serve as an indirect estimate or surrogate for loudness and that RT measurements are a useful tool to investigate loudness perception (e.g., Chocholle 1940;Stebbins 1966;Reason 1972;Moody 1973Moody , 1979Pfingst et al 1975a;Dooling et al 1975;Marshall and Brandt 1980;Buus et al 1982;Humes and Ahlstrom 1984;Seitz and Rakerd 1997;Leibold and Werner 2002;Arieh and Marks 2003;Wagner et al 2004;Florentine et al 2005;Little and May 2005;see also Scharf 1978;Luce 1986). Snodgrass (1975, p. 37ff) has even suggested that RT may be used more generally as an index of the magnitude of a listener's sensation.…”
Section: Simple Rt and Loudnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The general consensus, therefore, seems to be that there is a close relationship between loudness and RT. Consequently, it has been proposed that RT may serve as an indirect estimate or surrogate for loudness and that RT measurements are a useful tool to investigate loudness perception (e.g., Chocholle 1940;Stebbins 1966;Reason 1972;Moody 1973Moody , 1979Pfingst et al 1975a;Dooling et al 1975;Marshall and Brandt 1980;Buus et al 1982;Humes and Ahlstrom 1984;Seitz and Rakerd 1997;Leibold and Werner 2002;Arieh and Marks 2003;Wagner et al 2004;Florentine et al 2005;Little and May 2005;see also Scharf 1978;Luce 1986). Snodgrass (1975, p. 37ff) has even suggested that RT may be used more generally as an index of the magnitude of a listener's sensation.…”
Section: Simple Rt and Loudnessmentioning
confidence: 99%
“…Simple RT to auditory stimuli is commonly thought to be a measure of the loudness of the reaction stimuli, and is consequently viewed as a useful tool to study loudness perception (e.g., Chocholle 1940;Stebbins 1966;Moody 1973Moody , 1979Pfingst et al 1975a;Dooling et al 1975;Marshall and Brandt 1980;Buus et al 1982;Humes and Ahlstrom 1984;Seitz and Rakerd 1997;Leibold and Werner 2002;Arieh and Marks 2003;Wagner et al 2004;Florentine et al 2005;Little and May 2005;see also Scharf 1978;Luce 1986). In this context, it has been observed that plots of the sound levels of tones of different frequencies that evoked identical and very long mean RTs yielded curves in close proximity to, and of similar shape as, the animal's audiogram (e.g., Pfingst et al 1975a;Dooling et al 1975), suggesting that iso-RT contours for very long mean RTs might reflect the audibility curve.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter study, the inconsistency between loudness and RT was limited to lower loudness levels (20 phons) and may have been exacerbated by relatively sparse sampling of loudness matches and RT data. Additional studies have used the RT method to characterize the relationship between stimulus intensity and loudness in normal listeners (Marshall and Brandt 1980;Pins and Bonnet 1996), while others have pursued more complex perceptual phenomena such as loudness summation or adaptation (Arieh and Marks 2003). In general, where it is possible to make direct comparisons between RT and loudnessmatching procedures, results provide strong support for a close relationship.…”
Section: Reaction Time Studies Of Human Loudness Perceptionmentioning
confidence: 99%
“…By corollary, sounds with the same RT are interpreted to be equally loud. There is ample evidence that this metric is a useful tool for gauging loudness percepts in human subjects, for whom it is possible to make direct comparisons of conventional loudness estimates and RT measures (Marshall and Brandt 1980;Pfingst et al 1975) or to replicate well-established loudness effects (Arieh and Marks 2003;Florentine et al 2004;Wagner et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To summarize the evidence thus far: First, from a study that measured response times, we concluded that ILR represents a decrease in the magnitude of the suprathreshold sensory responsiveness rather than a decisional shift in response criteria (Arieh & Marks, 2003a). When listeners were asked to classify weak tones according to their frequency (high vs. low) in a speeded response task, stimulus conditions that were shown to produce ILR also produced longer response times and higher error rates.…”
mentioning
confidence: 98%